Reinventing Hubungan Birokrasi dan Politik dalam Mewujudkan Hubungan Industrial yang Berkeadilan di Indonesia: Suatu Kajian - Wandi, Wandi; Rifa'i, Ahmad (Universitas Batanghari, 2020)
Reinventing bureaucracy and politics must accommodate the tendency of bureaucratic political behavior. In short, public bureaucracy must be declared a political actor. As political actors, bureaucracy must not be neutral. He must increase the intensity of his involvement in the political process. However, the involvement of the public bureaucracy is not only oriented towards pursuing group profits solely. The involvement of bureaucracy in the political process and the bureaucracy's neutrality is the bureaucratic alignment of public interests such as economic progress, social justice, human rights, gender equality, and so on. Pancasila Industrial Relations as stated above can not be separated from the bureaucratic and political relations in a nation, therefore, it is important to do Reinventing Bureaucratic and Political Relations in realizing the democratization of industrial relations with justice in accordance with the values of Pancasila itself, namely by carrying out the Order Good governance.